Health and Economic Benefits of Ozone Reduction: Case Study in Santiago and Valparaíso - Espinoza-Perez, A; Campos-Bravo, V; Espinoza-Perez, L (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study estimated the relative risks (RRs) of respiratory and cardiovascular mortality and morbidity due to short-term ozone exposure in 13 polluted communes across Chile s Santiago Metropolitan and Valpara & iacute;so regions. Data on daily ozone, meteorology, and pollutants were sourced from the National Air Quality Information System (NAQIS), while health outcomes (mortality, hospital admissions, and emergency visits) were obtained from the Department of Health Statistics. A Poisson regression model, adjusted for trends, meteorology, day-of-week effects, and pollutants, quantified RRs for a 10 ppb ozone increase, ranging from 1.004 to 1.198 (95% CI). The highest risks were in Santiago s Eastern zone (cerebrovascular, RR 1.171, 95% CI: 1.018-1.347), Western zone (cardiovascular, RR 1.198, 95% CI: 1.049-1.369), and Valpara & iacute;so s Vi & ntilde;a del Mar (ischemic heart disease, RR 1.127, 95% CI: 1.017-1.248). The 5-64-year age group was most affected, particularly in terms of emergency visits. Reducing ozone to the WHO guideline (100 mu g/m3) could avoid 837,498 cases in Santiago and 17,992 in Valpara & iacute;so annually, resulting in economic savings of $7,439,930,640 and $1,044,568,800, respectively. These results highlight the need for stricter air quality policies to reduce ozone-related health burdens.